INFORMATION SYSTEM MEASUREMENT SUCCESS MODEL FOR E-PROCUREMENT (SPSE) IN GOVERNMENT AGENCY (Case Study : Ministry of F inance) - Nur Hakim, Lukman
Information system (IS) success measurement is a research that has been widely studied in the academic world. IS success is a tool to assess whether the investments and efforts made in implementing information systems in an organization to provide benefits or not as expected. This is even more crucial if the context is a government organization which is more important measure of success can not be measured directly. Electronic Procurement of Goods / Services Information System (SPSE) is an IS that used by Indonesian Government Agencies to procure goods/services using auction/selection method. SPSE aimed to improve efficiency, effectiveness, transparency, healthy competition and accountability in Procurement. This study aims to analyze the needs related to the measurement of the IS implementation success and designing a measurement model for the success of the IS implementation based on the DeLone and McLean model, UTAUT model and organizational culture model with a case study at the Ministry of Finance. The use of models is expected to produce a more comprehensive IS success model. The study was conducted through several stages of the identification and analysis of the needs of the design model, the measurement model success IS, data collection, design validation model use PLS-SEM. The results showed that the measurement IS success models is not good enough for measuring implementation SPSE at Ministry of Finance. From the hypotheses that have been developed, only five hypotheses have a strong influence, they are hierarchical culture toword effort expectancy, facilitating conditions toward use, intention to use toward use, information quality toward user satisfaction, and user satisfaction toward benefits with Tstatistic > 1.96.